Effectiveness and Safety of Metformin versus Canthex™ in Patients with Acanthosis Nigricans: A Randomized, Double-blind Controlled Trial - Sett, Arindam (Indian J Dermatol, 2019)
BACKGROUND: Acanthosis nigricans has been associated with conditions of insulin resistance such as obesity, polycystic ovary syndrome, and type 2 diabetes. Metformin and alpha-lipoic acid, two types of insulin-sensitizing agents, have been demonstrated to reduce insulin levels and improve insulin sensitivity. Alpha-lipoic acid is available as a fixed-dose combination with biotin, calcium pantothenate, and zinc sulfate as Canthex™. AIMS: This study aimed to compare the effectiveness, safety, and improvement of the insulin resistance profile of Canthex™ and metformin in acanthosis nigricans. MATERIALS AND METHODS: In this double-blind, randomized (1:1), active-controlled trial (CTRI/2017/02/007880), participants received either metformin 500 mg BD or Canthex™ BD for 12 weeks. Effectiveness parameters were improvement of severity of neck lesions and neck texture. Serum fasting insulin level, glucose, lipids, body weight, waist circumference, body mass index (BMI), and homeostatic model assessment-insulin resistance (HOMA-IR) were also assessed at baseline and at the end of the study. Adverse effects and changes in routine laboratory parameters were taken as safety parameters. RESULTS: Thirty-three patients were analyzed by modified-intention-to-treat criteria. Severity of neck lesions and texture were comparable at baseline and it showed significant reduction (P<0.001) in both the treatment arms from the first follow-up onward. No intergroup variation was observed in any of the follow-ups. There was reduction in the values of fasting insulin, blood sugar, total cholesterol, and thyroid-stimulating hormone in both the groups. Weight, BMI, and waist circumference and BMI reduced significantly in both the groups. HOMA-IR decreased significantly in metformin group (P<0.001). CONCLUSION: Canthex™ is as effective and safe as metformin in the management of acanthosis nigricans and associated features of insulin resistance.